Total Learning Experience Model as the Development of Geography Teaching Materials based on the Nature of the Grassroots Curriculum - Titi Syafura; Yurni Suasti; Ernawati Ernawati (International Journal of Educational Dynamics, 2021)
Learning geography still tends to use the lecture method. These learning conditions will result in not creating conducive learning and will have an impact on learning outcomes. Learning is a form of interaction between individuals and their environment so that they provide a lot of experience from real situations. The curriculum is a means to achieve the desired educational program. The solution that can be done is to apply the Grassroot curriculum system by developing teaching materials for the total learning experience model. Research by developing Research and Development (R & D) using the Dick & Carey model. The results obtained are that the development of the total learning experience model has high and efficient quality and legibility.